Noninvasive physiologic assessment of coronary stenoses using cardiac CT - Xu, L.; Sun, Zhonghua; Fan, Z. (Hindawi Publishing Corporation, 2014)
Coronary CT angiography (CCTA) has become an important non-invasive imaging modality in the diagnosis of coronary artery disease (CAD). CCTA enables accurate evaluation of coronary artery stenosis. However, CCTA provides limited information on the physiological significance of stenotic lesions. A noninvasive ‘one-stop-shop’ diagnostic test that can provide both anatomical and functional significance of stenotic lesions would be beneficial in the diagnosis and management of CAD. Recently, with the introduction of novel techniques such as myocardial CT perfusion, CT-derived fractional flow reserve (FFRCT), and transluminal attenuation gradient (TAG), CCTA has emerged as a non-invasive method for the assessment of both anatomy of coronary lesions and its physiological consequences during a single study. This review provides an overview of the current status of new CT techniques for the physiologic assessments of CAD.